The effect of sweat sample storage condition on sweat content - Klous, L.; Folkerts, M.; Daanen, H.; Gerrett, N. (Temperature, 2021)
Due to time and logistical constraints sweat samples cannot always be analyzed immediately. The purpose of this study was to investigate the effect of storage temperature and duration on sweat electrolyte and metabolite concentrations. Twelve participants cycled for 60 min at 40 W/m² in 33°C and 65% RH. Using the absorbent patch technique, six sweat samples were collected from the posterior torso. Sweat from the six samples was mixed, divided again over six samples and placed in sealed vials. Sweat sodium, chloride, potassium, ammonia, lactate and urea concentrations in one sample were determined immediately. Two samples were stored at room temperature (~25°C, 42% RH) for 7 and 28 days respectively. The remaining samples were frozen at -20°C for 1 h, 7 or 28 days respectively before analysis. Sweat sodium, chloride, potassium and urea concentrations were not affected by storage temperature and duration. Sweat lactate decreased (-1.8 ± 1.8 mmol/L, P = 0.007) and ammonia concentrations increased (5.1 ± 3.9 mmol/L, P = 0.017) after storage for 28 days at 25°C only. The storage temperature and duration did not affect sodium, chloride, potassium and urea concentrations. However, sweat samples should not be stored for longer than 7 days at 25°C to obtain reliable sweat lactate and ammonia concentrations. When samples are frozen at -20°C, the storage duration could be extended to 28 days for these components.